2013
DOI: 10.1063/1.4773820
|View full text |Cite
|
Sign up to set email alerts
|

Trapped charge dynamics in InAs nanowires

Abstract: We study random telegraph noise in the conductance of InAs nanowire field-effect transistors due to single electron trapping in defects. The electron capture and emission times are measured as functions of temperature and gate voltage for individual traps, and are consistent with traps residing in the few-nanometer-thick native oxide, with a Coulomb barrier to trapping. These results suggest that oxide removal from the nanowire surface, with proper passivation to prevent regrowth, should lead to the reduction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…This spacing is directly proportional to the charging energy which we conclude to be constant upon illumination. From Nakazato's model, we conclude that the hysteresis area change is then directly due to a modification of the time constant τ, pointing out to a modification in the dynamics of charge transfer through the MTJ, which is consistent with the work of Holloway et al Upon light exposure, the molecules involved in the MTJ turn excited which modifies the potential profile of the multiple barriers involved in the charge transfer to the nanotube. Indeed, Gruneis et al have observed sharp features in the case of a trap being very well coupled to a nanotube .…”
supporting
confidence: 87%
“…This spacing is directly proportional to the charging energy which we conclude to be constant upon illumination. From Nakazato's model, we conclude that the hysteresis area change is then directly due to a modification of the time constant τ, pointing out to a modification in the dynamics of charge transfer through the MTJ, which is consistent with the work of Holloway et al Upon light exposure, the molecules involved in the MTJ turn excited which modifies the potential profile of the multiple barriers involved in the charge transfer to the nanotube. Indeed, Gruneis et al have observed sharp features in the case of a trap being very well coupled to a nanotube .…”
supporting
confidence: 87%
“…While prototypical devices have demonstrated the fundamentals of this implementation [1,2,[11][12][13], further engineering is desirable to improve the reproducibility (less wire to wire variation), the tunability and stability of the electrostatic potential. Fluctuations in the electrostatic potential are largely due to charge traps located at the nanowire surface or in the native oxide layer [14,15]. Chemical passivation, in which a layer of atoms or molecules is covalently bonded to the semiconductor surface, is one method to prevent the oxide from forming and to passivate surface states.…”
Section: Introductionmentioning
confidence: 99%
“…Charge trapping by oxide at gate interfaces is a well-known contributor to gate hysteresis in nanowire transistors. [31][32][33] The data in Fig. 3b indicates low hysteresis under dc operation; this performance is retained under ac conditions also.…”
Section: Inspired By Mori Andmentioning
confidence: 83%